Turkish heritage families in Sweden: language practices and family language policy. Issue 9 (21st October 2022) - Bohnacker, Ute
ABSTRACT : This paper explores family language policy in Turkish-speaking families in Sweden. Questionnaires were administered to the parents of 105 Turkish/Swedish children (age 4 − 7), targeting family language practices (including parent–parent, parent–child, child–parent, child-and-sibling conversation and language-fostering activities such as joint book reading, storytelling and mother tongue tuition), and parental language beliefs and attitudes. Despite much diversity in family types concerning parents' education, country of birth, native language and ethnic affiliation (e.g. Kurdish), common traits emerge: There is a strong focus on the transmission of Turkish in the home, in the face of early and extensive Swedish pre-school attendance. Parents mostly speak Turkish with the child. However, Sweden-born parents report higher uses of Swedish in the home, and sibling interaction also drives a shift towards Swedish. Parental education appears to affect Turkish joint reading activities. Most parents consider proficiency in Turkish and Swedish as equally important for their children. Parents who rank Turkish higher do not necessarily show more maintenance efforts, pointing to some inconsistency between attitudes and practices. Overall, the family language practices observed indicate strong bilingual ideologies and strong language maintenance ideologies, in line with Swedish official state-level language policy, which supports bilingualism and minority language maintenance.